2014
DOI: 10.1002/stem.1812
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Delivery of Mesenchymal Stromal Cells Protects the Structure of Altered Perineuronal Nets in SOD1 Rats and Amends the Course of ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder resulting in a lethal outcome. We studied changes in ventral horn perineuronal nets (PNNs) of superoxide dismutase 1 (SOD1) rats during the normal disease course and after the intrathecal application (5 × 105 cells) of human bone marrow mesenchymal stromal cells (MSCs) postsymptom manifestation. We found that MSCs ameliorated disease progression, significantly improved motor activity, and prolonged survival. For the first time, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 70 publications
5
90
1
1
Order By: Relevance
“…In our previous study, we reported a prolonged lifespan and an improved neurological outcome in the SOD1 rats treated with hMSC in one single injection into cisterna magna at the onset of the disease. The animals survived on average 13.5 days longer than the PBS treated rats and no grafted cells were found 2 weeks after the application . The lifespan extension observed in our study was 18 and 19 days respectively for SC + M and SC groups.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In our previous study, we reported a prolonged lifespan and an improved neurological outcome in the SOD1 rats treated with hMSC in one single injection into cisterna magna at the onset of the disease. The animals survived on average 13.5 days longer than the PBS treated rats and no grafted cells were found 2 weeks after the application . The lifespan extension observed in our study was 18 and 19 days respectively for SC + M and SC groups.…”
Section: Discussionmentioning
confidence: 41%
“…Overall, this evidence suggests that necroptosis plays an important role in the development of ALS . We have previously reported the positive effect of a single application of hMSC into cisterna magna of SOD1 transgenic rats . In this study, we aimed to investigate the effect of repeated intrathecal applications of hMSC in a SOD1 transgenic rat model of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological ECM alterations have been described for ALS 94 and ALS model systems 95 . Our results showed consistent decreases in levels of ECM proteins, including tenascin R, agrin, and cell adhesion molecule 3.…”
Section: Discussionmentioning
confidence: 99%
“…Adherent cells during subsequent passages were differentiated into adipoblasts, osteoblasts, and chondroblasts. 12,13 Flow cytometry revealed strong positivity for CD90 and weak positivity for CD105, but cells were negative for CD3, CD34, CD45RA, and CD73 (Turnovcova, unpublished data, 2015). In culture, the cells were positive for CD90 and fibronectin and negative for CD11b and CD45.…”
Section: Mesenchymal Stem Cell Preparation and Labelingmentioning
confidence: 99%